2003
DOI: 10.1080/713847131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and Estrogen Replacement on Basal and Pelvic Nerve Stimulated Vaginal Lubrication in an Animal Model

Abstract: The goal of this study was to investigate the effects of ovariectomy and estrogen replacement on vaginal tissue integrity and vaginal lubrication in basal conditions and in response to pelvic nerve stimulation (PNS). Two weeks after ovariectomy, female New Zealand White rabbits were administered vehicle or estradiol (200 micrograms/day) for an additional 2 weeks. Ovariectomy caused significant vaginal atrophy and diminished vaginal lubrication in the basal state and after PNS, compared to intact controls. Estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Previous studies have demonstrated that estrogen deprivation by ovariectomy results in marked reductions in vaginal blood flow [4,15], vaginal epithelium thickness [3], vaginal lubrication [5], and ER␣ expression [4]. Furthermore, these studies demonstrated that estradiol treatment of ovariectomized animals restored the aforementioned structural, physiological, and biochemical parameters to control levels.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have demonstrated that estrogen deprivation by ovariectomy results in marked reductions in vaginal blood flow [4,15], vaginal epithelium thickness [3], vaginal lubrication [5], and ER␣ expression [4]. Furthermore, these studies demonstrated that estradiol treatment of ovariectomized animals restored the aforementioned structural, physiological, and biochemical parameters to control levels.…”
Section: Discussionmentioning
confidence: 93%
“…Androgens and estrogens regulate genital tissue growth and function and modulate genital blood flow [3][4][5][6]32]. Thus, androgen and estrogen insufficiency contribute to female genital sexual arousal dysfunction [3][4][5][6]32]. Several studies have reported decreased circulating estradiol levels in type 1 and type 2 diabetic animal models [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the treatment of FSAD has various options including hormone therapy, phosphodiesterase (PDE) inhibitors and alphablockers, mostly through enhancement of the vaginal blood flow [6,[8][9][10][11][12][13], they possess undesired side effects following their systemic administration. For examples, since PDE inhibitors and ablockers affected the systemic blood pressure and cardiac function, their clinical usages often resulted in adverse activities in cardiovascular regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory inputs from the pudendal nerve relay information relevant to mating that is received during anogenital investigation and mounting behavior and this input can trigger sexual arousal and lordosis [1,31,33,45,47]. The pelvic nerve conveys sensory information during vaginocervical stimulation, can modulate lordosis and is important in triggering hormonal changes that occur after mating in female rodents [23,24,32].…”
Section: Introductionmentioning
confidence: 99%